Elastic, structural and optical properties of zinc borotellurite glass system doped with europium oxide co-doped silver oxide nanoparticles - Adamu, Suleiman Bashir (2022)
Zinc borotellurite glasses doped with europium oxide and codoped silver oxide nanoparticles have been extensively investigated in terms of their structural and optical properties. However, their mechanical properties, Judd-Ofelt analysis, and artificial neural network simulation have not been extensively studied. In this study, four glass series of zinc borotellurite doped with europium oxide (Eu2O3) and europium oxide nanoparticles (Eu2O3 NPs), and co-doped silver oxide nanoparticles (Ag2O NPs)/Eu2O3 and Eu2O3 NPs /Ag2O NPs, were successfully prepared by using the melt-quenching method. The glasses were synthesized using a chemical composition formula of [{(TeO2)0.7(B2O3)0.3}0.7(ZnO)0.3](1-x) (Eu2O3/Eu2O3 NPs)x, where x = 0.01 to 0.05 molar fraction and [{(TeO2)0.7 (B2O3)0.3}0.7 (ZnO)0.3]0.96 (Eu2O3/Eu2O3 NPs)0.04](1-y) (Ag2O NPs)y where y = 0.0011 to 0.0015 molar fraction. The glass series is coded Eu2O3, Eu2O3 NPs, Ag NPs (Eu), and Ag NPs (Eu NPs). The glasses were characterised by X-ray diffraction (XRD), Fourier transforms infrared spectroscopy (FTIR), transmission electron microscopy (TEM), ultrasonic, ultravioletvisible near-infrared and photoluminescence (PL) spectroscopy. The XRD results show a board hump at lower diffraction angles ranging from 20° to 40° (2θ), with no sharp peaks, indicating an amorphous solid characteristic. FTIR results revealed structural units of TeO3, TeO4, BO3, and BO4. Furthermore, the existence of Eu2O3 NPs and Ag2O NPs was confirmed by TEM morphology images. On the other hand, the density of all the glass series Eu2O3 and Eu2O3 NPs increased from 4.744 to 5.153 g/cm3 and from 4.675 to 4.948 g/cm3, respectively, while the molar volume increased from 24.58 to 25.61 cm3/mol, and from 25.34 to 26.07 cm3/mol, respectively. In contrast, the density of the Ag NPs (Eu) and Ag NPs (Eu NPs) glasses increased, while their molar volumes decreased. Their respective values ranged from 4.806 to 4.834 g/cm3, from 26.372 to 26.128 cm3/mol and from 4.735 to 4.855 g/cm3, and from 26.767 to 26.115 cm3/mol. Additionally, the theoretical and experimental elastic moduli and ultrasonic velocity increased as the dopant concentration increased. Furthermore, ring deformation provides excellent, consistent results in all glass series that match the experimental elastic modulus among all theoretically elastic models calculated. Moreover, using an artificial neural network (ANN) model, the density and elastic characteristics were predicted and simulated. The correlation coefficients for density and elastic moduli computed with the ANN model vary from 0.9532 to 0.9999. The estimated percentage error is less than 8%, while the squared R fitted value is more than 95%. Furthermore, both the direct and indirect bandgap energies of Eu2O3, Eu2O3 NPs, Ag NPs (Eu), and Ag NPs (Eu NPs) glasses all show consistent decreases as the dopant concentration increases. In contrast, Urbach's energy and refractive index values increase with increasing dopants content. Furthermore, the Judd-Ofelt intensity and radiative transition parameters were calculated from the PL data. The results revealed 5D0 →7F2 ED transition exhibits the highest radiative properties, such as branching ratio (βr) and stimulated emission cross-section (σse). These parameters for Eu2O3 glasses range from 54.03 to 66.54 % and 10.039 to 14.029 × 10-22 cm2, for Eu2O3 NPs from 57.61 to 67.82 % and 12.099 to 14.765 × 10-22 cm2, for Ag NPs (Eu) from 57.233 to 68.756 % and 13.172 to 19.285 × 10-22 cm2 and for Ag NPs (Eu NPs) glasses from 58.645 to 69.073% and 12.914 to 20.760 × 10-22 cm2, respectively. Additionally, the CIE colour coordinate values are found in the white-light region and glass samples, Eu2O3-0.04, Eu2O3 NPs- 0.04, Ag NPs (Eu) 0.0015, and Ag NPs (Eu NPs) 0.0015, are considered potential candidates for white light-emitting devices. Besides, among all glasses, the Ag NPs (Eu NPs) series exhibits significant βr and σse, thus exhibiting high potential for tunable lasing under an excitation of 375 nm. Therefore, it is considered the best host for laser or white light applications.